1989
DOI: 10.1161/01.str.20.5.592
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic markers in acute stroke.

Abstract: To assess the time course of thrombosis and fibrinolysis after acute stroke, we measured concentrations of fibrinopeptide A (FpA), B-/3 1-42 peptide (B-0 1-42), B-0 15-42 peptide (B-/3 15-42), and crosslinked D-dimer (XDP) hi 31 patients at varying times following acute ischemic stroke and in 13 neurologically stable patients with chronic strokes. FpA levels were markedly elevated during the first week after stroke and declined slowly during the first month. Mean FpA levels were not significantly elevated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 32 publications
4
62
1
1
Order By: Relevance
“…1 presents the D-dimer and stroke volume data, describcomes using the modified Rankin Scale (mRS) and modified Glasgow Outcome Scale (GOS), which places the scores in reverse order. To analyze the initial NIHSS results, we divided the patients into three categories according to this baseline NIHSS score : mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe (16 and above) 1,38) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 presents the D-dimer and stroke volume data, describcomes using the modified Rankin Scale (mRS) and modified Glasgow Outcome Scale (GOS), which places the scores in reverse order. To analyze the initial NIHSS results, we divided the patients into three categories according to this baseline NIHSS score : mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe (16 and above) 1,38) .…”
Section: Resultsmentioning
confidence: 99%
“…Plasmin splits the fibrin into FDP and D-dimers when the coagulation and fibrinolytic system is activated. A number of studies have shown that D-dimer, C-reactive protein, and other markers of hemostatic activation associate with a stroke diagnosis 5,18,19,[21][22][23]28,31,35,39) and with progression and death in acute ischemic stroke 5,6,10,30,44) . The report by Laskowitz et al 22) suggests that a biomarker panel may add valuable and time-sensitive diagnostic information to early stroke evaluation and rapid identification of patients with suspected stroke, which would expand the availability of time-limited treatment strategies.…”
Section: Treatmentmentioning
confidence: 99%
“…D-dimer levels are elevated in venous thrombosis, 40 pulmonary embolism, 41 stroke, 42 and myocardial infarction, 43 with additional evidence that increased D-dimer levels may be a marker of subsequent thrombotic events. 44 Our finding of significantly …”
Section: Discussionmentioning
confidence: 99%
“…Impaired fibrinolytic activity has been reported in various systemic atherothrombotic disorders. 6 " 818 It is possible that thrombotic process develops on atherosclerotic plaques as a consequence of local activation of coagulation, which easily may be brought about by some unknown stimuli under the prethrombotic state. Such phenomena may also be accelerated by endogenous fibrinolytic insufficiency or plasma hypercoagulability during acute stage of atherothrombotic stroke.…”
Section: Discussionmentioning
confidence: 99%